Estimating the impact of animal health and death loss on economic performance of feedlot cattle - M. Irsik; Michael R. Langemeier (Kansas Agricultural Experiment Station Research Reports, 2003)
This study examined the impacts of animal health and death loss on the economic performance of feedlot cattle. Using data from two feedlots in western Kansas, the impact of animal health on economic performance was quantified. Death loss and the percentage of animals treated significantly impacted feed conversion, average daily gain, and cost of gain. Feed conversion for a pen of cattle was found to increase by 0.27 lb feed/lb gain and daily gain decreased by 0.08 lb/day for each percentage point increase in death loss. An increase in death loss from 1% to 2% increased cost of gain by 2.29/100 lb gain.
Keywords: Cattlemen& #x27; s Day; 2003; Kansas Agricultural Experiment Station contribution; no. 03-272-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 908; Beef; Animal health; Death loss; Economic performance; Feedlot cattle